2016
DOI: 10.1017/age.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Motivations Driving Organic Demand: Between Self-interest and Sustainability

Abstract: We study consumers' motivations for buying organic food by analyzing their shopping baskets. Buying organic can be motivated by concern about sustainable development and/or self-interest (considerations related to health or product quality). Pro-social motivation is inferred from the presence of fair trade products in the consumer's basket; consumer self-interest is deduced from the presence of healthy and higher-quality products bearing special quality labels or certifications. Our results indicate that envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Azurra et al's [91] research confirmed the authors' assumption that consumers who prefer organic products show a higher level of concern for sustainability when making overall dietary choices and lead to more sustainable lifestyles. According to Monier Dilhan and Bergès [92], the results presented suggest that consumers involved in purchasing organic foods appear to be strongly motivated by public variables such as environmental and social. Personal benefits such as health and quality also have a large impact on the choice of foods.…”
Section: Discussionmentioning
confidence: 92%
“…Azurra et al's [91] research confirmed the authors' assumption that consumers who prefer organic products show a higher level of concern for sustainability when making overall dietary choices and lead to more sustainable lifestyles. According to Monier Dilhan and Bergès [92], the results presented suggest that consumers involved in purchasing organic foods appear to be strongly motivated by public variables such as environmental and social. Personal benefits such as health and quality also have a large impact on the choice of foods.…”
Section: Discussionmentioning
confidence: 92%
“…Many consumers believe that organic foods are healthier and taste better, in addition to being better for the environment (Monier‐Dilhan & Berges, ). Do those perceptions extend to beer?…”
Section: Introductionmentioning
confidence: 99%
“…A conventional drying process such as convective air-drying allows to extend shelf life considerably, but not without loss of nutritional and sensory qualities of the berry [35]. Recent mild processing technologies (e.g., microwave-vacuum) are able to dry the berries while preserving their nutritional quality by retaining more of the initial ascorbic acid, anthocyanins and phenolic compounds, and antioxidant capacity [36][37][38].Organic foods are a product category that consumers perceive to be healthy [39][40][41]. Indeed, a large number of studies show that organic consumers' choices are mainly driven by the perceived naturalness and healthiness of these products compared to conventional food products [41][42][43][44][45][46][47][48].…”
mentioning
confidence: 99%
“…Organic foods are a product category that consumers perceive to be healthy [39][40][41]. Indeed, a large number of studies show that organic consumers' choices are mainly driven by the perceived naturalness and healthiness of these products compared to conventional food products [41][42][43][44][45][46][47][48].…”
mentioning
confidence: 99%